ETHNOMATHEMATICS EXPLORATION IN THE TRADITIONAL ART OF RANDAI MINANGKABAU - Miftahurrahmi, Miftahurrahmi; Pratiwi, Is Oktaria; Huda, Fajrul; Habibi, Mhmd (KALAMATIKA Jurnal Pendidikan Matematika, 2024)
Mathematics is a scientific field that delves into numbers, measurements, and formulas. When mathematical concepts intertwine with culture, it forms what is known as ethnomathematics. Integrating mathematics with cultural elements can significantly enhance the learning experience. This research aims to identify and elucidate mathematical elements in the traditional Minangkabau art form of Randai. The methodology employed in this study is qualitative descriptive, utilizing a library research approach. No field studies were conducted; the research relied solely on a literature review. The data utilized comprises documents derived from studies of Randai art and other written references relevant to the research problem. The researcher serves as the primary instrument, indispensable to this study. Data collection methods include documentation and an extensive literature review. The findings reveal that traditional Minangkabau randai art encompasses not only artistic expression but also philosophical insights, cultural values, and mathematical elements, known as ethnomathematics. Ethnomathematics manifests in Randai art through its form, spatial dimensions, and musical instruments.